1-D and 2-D phosphine coordination materials based on a palladium(II) PCP pincer metalloligand. (15th March 2018) - He, Junpeng; Bohnsack, Alisha M.; Waggoner, Nolan W.; Dunning, Samuel G.; Lynch, Vincent M.; Kaska, William C.; Humphrey, Simon M.
Graphical abstract: A para -carboxylated PCP-pincer has been designed for the subsequent construction of crystalline porous coordination polymer materials. After cyclometallation with PdCl2, the resulting metalloligand can be used to prepare materials with 1-D (chain) and 2-D (sheet) networks. The 2-D material display permanent porosity and reversible gas uptake in the solid-state. Abstract: Ancillary functionalization of a PCP pincer ligand with para -carboxylic acids provides a simple route to the subsequent preparation of crystalline coordination polymers using pre -cyclometallated complexes as polymer building blocks. This synthetic strategy is demonstrated here using air- and moisture-stable PCP-PdCl metalloligands to prepare new coordination polymers with both 1-D (chain) and 2-D (sheet) networks, named PCM-29 and PCM-30, respectively. The single crystal X-ray structures and solid-state gas sorption properties of both materials are presented. The Brunauer-Emmett-Teller (BET) surface area of PCM-30 was found to be 302 m 2  g −1 using CO2 as the probe gas, indicating permanent porosity and reversible small molecule diffusion between the 2-D sheets.